Idyll and History in Little Russia Representation (Based on “Journey of Professor Pogodin Abroad in 1842” by M. P. Pogodin) - Sergey S. Zhdanov (Два века русской классики)
The article examines the representation of the space of Little Russia in M. P. Pogodin’s “Trip of Pr<ofessor> Pogodin Abroad in 1842.” Two local types represent it. Firstly, it is the space of the idyll, marked by the motives of attractiveness, abundance, space, naturalness, and freedom. This topos is of particular importance if we talk about the description of these topos regarding the Little Russian House-Garden. This type is associated with the image of the Little Russian peasant as a “natural man” free from the vices of civilization. Gogol’s text acts as an additional literary prism through which the narrator looks at the idyllic Little Russia. Secondly, Little Russia acts as a space of historical memory, i. e., linear rather than achronic-idyllic time, which actualizes, in particular, the motive of oblivion. The historical sphere of characters is represented by several figures from the era of Vladimir I to the 19th century.